Autonomy over Life: The Struggle against Capitalist Development in West Papua - Samira Homerang Saunders; Angela Sherwood; David Whyte (State Crime)
West Papua—the part of the island of Papua currently ruled by Indonesia—is a site of aggressive industrial development, with major industries in gas extraction, metallurgical mining, and agricultural plantation. It is also home to the third largest rainforest area in the world after the Amazon and Congo basins. This article analyzes the struggle by the Papuan people to resist the rapidly accelerating form of industrial development that is being imposed on them against their will. It highlights how extreme forms of state violence and a politically imposed settlement, against the will of the Papuan people, fuel an ongoing conflict. The article therefore argues that demands for the right to self-determination as a form of political autonomy cannot be separated from the struggle to retain basic control over the essential conditions for life in West Papua: food production and the protection of water and air quality. Moreover, it argues that resistance to the Indonesian state in West Papua must be understood as a struggle for autonomy in the widest possible sense: a struggle to assert autonomy over the entirety of social and economic reproduction.